THE EFFECT OF PSYCHOLOGICAL AND HEALTH EDUCATION APPROACHES BASED ON SELF-EFFICACY ON COMPLIANCE WITH TUBERCULOSIS PATIENT: A SYSTEMATIC REVIEW - Idham Choliq; Tintin Sukartini; Makhfudli Makhfudli (Nurse and Health: Jurnal Keperawatan, 2020)
Background: One of the obstacles to TB management today has been non-compliance. Non-compliance of TB patients in treatment can be influenced by the perception of self-efficacy.Objective: The study aimed to analyze the effect of psychological and health education approaches based on self-efficacy on adherence with tuberculosis patients.Design: Design research uses systematic review based on PRISMA checklist.Data Sources: Using three databases: Scopus, Science direct, and CINAHL. The three databases are of high and medium reputation. The search was conducted from June to July 2020. The keywords in this systematic review are “mycobacterium tuberculosis” OR "tuberculosis" OR "pulmonary TB", "adherence OR Compliance" and "psychology OR health education OR self-efficacy". Searching are limited to journal articles, 2012-2020 publication years and English language articles.Review Methods: To assess the quality of articles is using the JBI Critical Appraisal Tool and PRISMA checklist as a guide to filter articles.Results: A total of 10 articles were analyzed according to inclusion criteria. The results obtained as many as 6 studies are randomized control Trials, 2 studies use Quasi-Experiment, and 2 observational studies. The number of samples varied from 19 to 361 respondents. Age from 15 to 65 and above. Gender characteristics are dominated by men and the study was multi-regional. and most levels of education at the elementary and junior high school levels. The psychological and health education approaches based on self-efficacy are divided into several approaches that are proven to increase compliance including: psychotherapy, mindfulness, counseling and education, Medication Adherence Enhancement Program (MAEP).Conclusion: Psychological approaches and Health Education based on self-efficacy consist of various interventions. The articles analyzed mostly use the HBM concept. There needs to be a self-efficacy development program that not only emphasizes the individual and cognitive, but also needs social and family support in improving self-efficacy, so that it affects the effectiveness of treatment. Keywords: Mycobacterium Tuberculosis, Compliance, Psychology, Health Education, Self-Efficacy.